A new species of the genus Toleria Walker, 1865 [“1864”] from Vietnam, with a catalogue of Asian Cissuvorini (Lepidoptera: Sesiidae) - Gorbunov, Oleg G.; Arita, Yutaka (Zootaxa, 2020)
A new clearwing moth species, Toleria vietnamica sp. nov. from Ba Bể National Park, Bẳc Kan Province, North Vietnam is described and illustrated. An annotated catalogue of Asian members of the tribe Cissuvorini is added to this paper. The catalogue contains the following information: the references to the original descriptions, information on name-bearing types, complete bibliographies of the presented taxa, distribution and available data on host plants. The type series of the new species is deposited in the collection of National Museum of Nature and Science, Tsukuba (formerly Natural Science Museum Tokyo).